A comparison of floating and sunken media biological aerated filters (BAF) - Mann, Allan (Cranfield University, 1997)
The aim of this experimental work was to directly compare the performance of two types of media support in pilot scale biological aerated filter (BAF) reactors. The two media types were identical in shape and size except one was sunken with a relative density of 1.05 and the other floating with a relative density of 0.92 and made of polypropylene. Empty bed tracer studies were initially undertaken to ascertain the hydraulic characteristics of the media types under different process conditions. Almost ideal plug-flow was seen without aeration but with aeration some mixing and by-passing was seen which increased with higher aeration rates. Aerator design and positioning had little effect on the flow and that the sunken media would perform best in downflow and the floating media in upflow during biological treatment. Two methods of start-up were employed during unsteady state analysis, activated sludge seeding and the use of the process liquid (settled domestic sewage) at the operational flowrate. Both methods showed a similar total start-up time of 28 d. At steady state the floating media removed 78% suspended solids (SS) and 75% soluble chemical oxygen demand (sCOD) compared to 66% and 68% respectively in the sunken media. At high flowrates and during shock loadings of up to 1.5 times the nominal flowrate the floating media again showed a better performance than the sunken media. With increasing shock loadings the recovery time increased with a corresponding decrease in solids and soluble COD removal rates. At the maximum SS loading of 1.397 kg m'3 d'1 ( 1.403 kg m"3 d'1 sCOD) only 35% (30% sCOD) removal was seen in the sunken media compared to 60% (40% sCOD) in the floating media. The steady state results were used to produce an empirical model relating effluent soluble COD to influent COD and reactor height. Assuming plug flow the profiles showed a first order rate of reaction. A first order empirical model was then established based on that used for trickling filters, which produced constants dependent on the media type. During tertiary treatment low ammonia loadings of 0.2 kg m'3 d"1 restricted autotrophic growth and led to preferential growth of heterotrophic bacteria. At ammonia loadings of up to 1.16 kg m'3 d"1 nitrification was rapid. Below 5 °C nitrification was minimal but almost full nitrification was achieved at approximately 10 °C. Though backwashing was carried out only on a weekly basis, overwashing appeared to have caused a gradual reduction in treatment efficiency. During nitrification the sunken media was more efficient at ammonia removal than the floating media, indicating that the autotrophic bacteria prefer the more open structure of the sunken media. Reactor profiles indicated a zero to half order reaction.